2017
DOI: 10.1007/s00268-017-4182-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Safety of Renaming Encapsulated Follicular Variant of Papillary Thyroid Carcinoma: Is NIFTP Truly Benign?

Abstract: Our study demonstrates that the incidence of NIFTP is significantly lower than previously thought. Furthermore, evidence of malignant behavior was seen in a significant number of NIFTP patients. Although the authors fully support the de-escalation of aggressive treatment for low-risk thyroid cancers, NIFTP behaves as a low-risk thyroid cancer rather than a benign entity and ongoing surveillance is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
94
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(99 citation statements)
references
References 18 publications
3
94
1
1
Order By: Relevance
“…In the initial study defining NIFTP, the authors confirmed the very low recurrence risk for NIFTP on the basis of a retrospective analysis of cases with long‐term follow‐up. However, a subset of subsequent studies have demonstrated that a small percentage of patients with lesions seeming to satisfy the diagnostic criteria for NIFTP develop regional lymph node metastases . Rosario et al reported that 1 of 45 NIFTP patients in their cohort developed a lymph node metastasis, although that patient also had a concurrent papillary thyroid microcarcinoma.…”
Section: Limitations and Changes In The Terminology: Results Of The Chmentioning
confidence: 99%
See 1 more Smart Citation
“…In the initial study defining NIFTP, the authors confirmed the very low recurrence risk for NIFTP on the basis of a retrospective analysis of cases with long‐term follow‐up. However, a subset of subsequent studies have demonstrated that a small percentage of patients with lesions seeming to satisfy the diagnostic criteria for NIFTP develop regional lymph node metastases . Rosario et al reported that 1 of 45 NIFTP patients in their cohort developed a lymph node metastasis, although that patient also had a concurrent papillary thyroid microcarcinoma.…”
Section: Limitations and Changes In The Terminology: Results Of The Chmentioning
confidence: 99%
“…Rosario et al reported that 1 of 45 NIFTP patients in their cohort developed a lymph node metastasis, although that patient also had a concurrent papillary thyroid microcarcinoma. Parente et al reported that 5 of their NIFTP cohort cases (4.9%) were associated with lymph node metastases, and 1 case developed a distant metastasis. In their cohort of 152 NIFTP cases, Cho et al described 105 cases that had isolated papillary structures, which represented less than 1% of the tumor according to NIFTP criteria.…”
Section: Limitations and Changes In The Terminology: Results Of The Chmentioning
confidence: 99%
“…For the ThyroSeq cohort, we had relatively few cases that demonstrated HR mutations, reflecting that the majority of the cases in the current study (83%) were negative for mutations. We had a small number of NIFTP cases, which is in keeping with other studies demonstrating that a diagnosis of NIFTP is relatively rare if strict criteria are applied for diagnosis . With regard to our assessment of ultrasound features and size within the context of molecular testing, because the current study is pathology focused, we reviewed ultrasound reports to assign nodules to ATA 2015 sonographic patterns rather than reviewing the ultrasound images themselves.…”
Section: Discussionmentioning
confidence: 97%
“…However, this is not to say that these results are necessarily “false‐positives” for the cases classified on surgical resection as NIFTPs. This is an important point to remember when considering the results of all of these studies: to our current understanding, NIFTP is a lesion that, although indolent, nevertheless warrants at least conservative surgical excision, both for diagnosis and management . Therefore, in the case of NIFTP, the Afirma GEC and ThyroSeq tests still are successfully identifying patients who would potentially still require surgical management.…”
Section: Discussionmentioning
confidence: 99%
“…The extent of all the changes related to the NIFTP reclassification apparently depends on the incidence of NIFTP in a certain population. Approximately, 30 studies have been conducted in America, Europe and Asia reporting variable incidence . Bychkov et al, in a meta‐analysis, documented an average worldwide prevalence rate of 9.1%, with a lower rate in Asian studies (1.6%) as compared with non‐Asian countries (13.3%) .…”
Section: Discussionmentioning
confidence: 99%